Collaborative Writing in L2 Classrooms - Dennis Koyama (Working Papers in Applied Linguistics and TESOL, 2015)
With the appearance and improvement of Web 2.0 technology and other digital tools such as Google Docs and wikis, teachers and researchers are increasingly able to implement collaborative activities in face-to-face and online language courses. Whether technologically assisted or done in person, collaboration is a burgeoning area of investigation in L2 writing research and practice. Although many researchers and teachers alike still consider writing an independent activity, Collaborative Writing in L2 Classrooms has taken the charge to illuminate the potential advantages of employing collaborative writing in language research and by extension pedagogical practice. To do so, Storch offers a comprehensive review of the current research on L2 collaborative writing, while identifying that there remains theoretical uncertainty concerning how writing tasks affect the product and process of collaborative writing across and within learner contexts, and how the formation of collaborative pairs and groups may change the nature of the collaborative writing project. By discussing these issues and advocating for the guided use of collaboration in L2 writing research, Storch eloquently builds a bridge to span the gulf between collaborative activities L2 research (which has predominantly been used for aural and oral task) and the domain of L2 writing. Storch presents compelling theoretical, empirical, and pedagogical rationales in this well-written analysis of the research on writing in L2 classrooms, and she provides useful recommendations and caveats to researchers and teachers.